Pemberdayaan Ekonomi Komunitas Muslim Melalui Bank Sampah - Rihlah Nur Aulia; Rihlah Nur Aulia; Izzatul Mardhiah; Sari Narulita; Nur Amanah (Jurnal Studi Al-Quran, 2015)
This research is motivated by the empowerment of Muslim community through majlis talim or recitation group of mothers in the field of religion and social empowerment of society and its member economics in solving the environmental problems and protection of nature and natural resources can not be solved only by relying on knowledge and technology. Environmental problems and crises can only be overcome by fundamental and radically changing the way people view and behave towards their natural environment. What is needed is a change of perspective and behavior that is not only an individual, but it must be a culture of society at large. The main purpose of this study is to find out how the model of empowerment of Muslim community conducted by the group of majlis talim alkaromah dikelurahan Pejuang sub district Medan satria Bekasi.